The Role of Rapid Endoscopy for High-Risk Patients with Acute Nonvariceal Upper Gastrointestinal Bleeding - Laura E Targownik; Sanjay Murthy; Leila Keyvani; Shauna Leeson (Canadian Journal of Gastroenterology)
BACKGROUND: Performance of endoscopy within 24 h is recommended for patients with acute nonvariceal upper gastrointestinal bleeding (ANVUGIB). It is unknown whether performing endoscopy early within this 24 h window is beneficial for clinically high-risk patients.